Influenza vaccination prevalence among the elderly and individuals with chronic disease, and factors affecting vaccination uptake - Korkmaz, Pinar; Paşali Kilit, Türkan; Onbaşi, Kevser; Mistanoglu Ozatag, Duru; Toka, Onur (Central European journal of public health, 2019)
OBJECTIVE: Our aim is to evaluate influenza vaccination rates among the elderly and individuals with underlying chronic disease, and factors that affect vaccination uptake. METHODS: The study comprised individuals aged 18-65 years with underlying chronic diseases, and individuals aged over 65 years. Literature-based questionnaires prepared by the researcher regarding vaccination were completed through face-to-face interviews by the principal investigator. RESULTS: A total of 818 participants were included in the study, 257 (31.4%) were males. The mean age of participants was 57.47 ± 14.11 years; 274 (33.5%) were aged 65 years and over. One hundred and three (12.6%) participants stated that they received vaccinations against influenza annually, and 144 (17.6%) stated that they had vaccination against influenza in the 2015/16 or 2016/17 season. Fifty-two (19%) participants aged more than 65 years stated that they received vaccinations against influenza annually, 75 (27.4%) stated that they had vaccination against influenza in the 2015/16 or 2016/17 season. The most commonly determined reasons for not receiving vaccination were not knowing that it was necessary (34%) and believing that vaccination was not necessary because they were healthy (26%). Statistically significantly more participants who gained their knowledge from a physician were vaccinated than those whose knowledge came from other sources (p < 0.05). Participants who considered that they had sufficient information about influenza were vaccinated more frequently, the results were statistically significant (p < 0.05). CONCLUSION: Informing target risk groups about influenza vaccination by physicians and increasing awareness about influenza may contribute to increasing vaccination rates.
Keywords: senioři; Interviews as Topic; pacientův souhlas se zdravotní péčí; Prevalence; senioři nad 80 let; mladiství; Chronic Disease; vakcíny proti chřipce; chronická nemoc; Influenza, Human; Middle Aged; mužské pohlaví; prevalence; Vaccination; chronic disease; vakcinace; Adult; mladý dospělý; Influenza Vaccines; risk group; influenza; Health Knowledge, Attitudes, Practice; Aged, 80 and over; Young Adult; ženské pohlaví; Humans; chřipka lidská; lidé středního věku; rozhovory jako téma; elderly people; dospělí; zdraví - znalosti, postoje, praxe; Female; Aged; Adolescent; Patient Acceptance of Health Care; lidé; Male; vaccination